The Relationship between Self-Confidence and Arabic Speaking Skills among Arabic Education Students - Yolanda Selvy; Budi Sanjaya; Putri Hardiyanti (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2026)
This research aims to determine the level of students’ self-confidence, the level of Arabic speaking skills proficiency, and the relationship between self-confidence and speaking skills in Arabic language learning. This study employed a quantitative correlational design using random sampling. The subjects were students of the Arabic Language Education Study Program at Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi. A total of 63 students completed the self-confidence questionnaire, while 54 students were selected for the speaking test based on the Krejcie and Morgan sample size table. Data were collected through a Likert-scale questionnaire and an Arabic speaking interview test, then analyzed using descriptive statistics and Pearson Product Moment correlation. The results show that the students’ self-confidence level is in the high category (M = 3.43, SD = 0.69), with the self-efficacy and resilience aspects obtaining the highest average scores (M = 3.82, SD = 0.68) and (M = 3.64, SD = 0.55), while the social anxiety aspect shows the lowest score (M = 2.83, SD = 0.80). Students’ speaking proficiency is generally categorized as good, with the highest percentages found in comprehension (56.3%) and pronunciation (51.6%), although variations still appear in vocabulary and fluency aspects. The correlation test results indicate that the relationship between self-confidence and speaking skills is positive but very weak and not statistically significant (r = 0.161; p = 0.246). These findings suggest that self-confidence alone does not significantly influence students’ Arabic speaking ability without support from other linguistic and pedagogical factors. In addition, the findings highlight the importance of integrating psychological and instructional aspects in improving Arabic speaking competence among university students.